The effect of the essential oils from five different Lippia species on the viability of tumor cell lines - Gomide,Mayna da S. (2013)
Several Lippia species have been used in folk medicine mainly for gastrointestinal and respiratory diseases. Their biological properties have been partially associated to the terpenoids found in their essential oils. According to the World Health Organization, cancer is the leading cause of death worldwide and is described as a complex group of diseases with several hallmarks. One of its acceptable defining features is the cell proliferation beyond their boundaries forming the tumors. Importantly, some drugs currently available were discovered by the investigation of plant secondary metabolites. Thus, this study aimed to evaluate in vitro cytotoxic effect of the essential oils extracted from five Lippia species against tumor cell lines. The results indicated that mouse colon carcinoma CT26.WT cell line viability was significantly reduced showing an IC50 of 19.05, 30.20 and 36.30 µg/ml when treated with the essential oils of L. sidoides, L. salviifolia and L. rotundifolia, respectively. Human lung carcinoma A549 cell line also had a compromised viability to the action of L. alba carvone chemotype essential oil. The tested essential oils did not compromise viability of the normal cell line CHO. These finds suggest that the studied Lippia essential oils might be good candidates for further in-depth studies.